Managerial competencies scale in a public management context: development and validation evidences - Paz, Luísa Magalhães Coelho Ávila; Odelius, Catarina Cecília (Organizações & Sociedade, 2021)
The purpose of the study was to develop and present validation evidences for a managerial competence mastery scale in the context of public management. The development of the initial instrument for data collection was based on literature analysis, and on theoretical and semantic validation made by judges, in addition to a pre-test. The questionnaire was electronically answered by 447 professionals—managers and non-managers—that belong to different public companies that works at the state level, engaged in technical assistance and rural extension. The results of exploratory factorial analysis presented signs of validity and reliability, indicating thirty competency items that were grouped into three factors: contribution for strategy, public service rendering and team management. As conclusion, the evidence indicates the validity of the scale to measure the managerial competence mastery, contributing to the evolution of managerial studies and increasing the reliability thereof. Additionally, the identified competencies reinforce the role of the managers in the alignment and management of organizational strategy, they indicate the existence of common characteristics of managers that work in different organizations and also demonstrate the adequacy of this instrument to the public sector reality. Finally, the use of the scale is suggested in other research contexts in order to confirm its structure and generalization potential.